Identification of Escherichia coli through analysis of 16S rRNA and 16S-23S rRNA internal transcribed spacer region sequences - Magray, Mohammed Siraj Ud Din (Biomedical Informatics, 2011)
A bacterial strain, designated BzDS03 was isolated from water sample, collected from Dal Lake Srinagar. The strain was characterized by using 16S ribosomal RNA gene and 16S-23S rRNA internal transcribed spacer region sequences. Phylogenetic analysis showed that 16S rRNA sequence of the isolate formed a monophyletic clade with genera Escherichia. The closest phylogenetic relative was Escherichia coli with 99% 16S rRNA gene sequence similarity. The result of Ribosomal database project's classifier tool revealed that the strain BzDS03 belongs to genera Escherichia.16S rRNA sequence of isolate was deposited in GenBank with accession number FJ961336. Further analysis of 16S-23S rRNA sequence of isolate confirms that the identified strain BzDS03 be assigned as the type strain of Escherichia coli with 98% 16S-23S rRNA sequence similarity. The GenBank accession number allotted for 16S-23S rRNA intergenic spacer sequence of isolate is FJ961337.